(untitled) (Journal of the Bangladesh Agricultural University, 2012)
The effect of different rates of boron application on wheat cv. Bijoy was studied through a field experiment at Bangladesh Agricultural University (BAU) farm, Mymensingh during 2009-10 rabi season. The BAU farm belongs to Old Brahmaputra Floodplain agroecological zone (AEZ 9). Texturally the soil was silt loam, with 7.2 pH, 0.81% organic matter and 0.15 mg kg-1 available boron content. The experiment was laid out in a randomized complete block design with five boron rates and four replications. Boron rates were 0, 0.75, 1.5, 2.25 and 3.0 kg ha-1, with boric acid as a source. Every plot received blanket doses of 115 kg N, 25 kg P, 75 kg K and 15 kg S ha-1 from urea, TSP, MoP and gypsum, respectively. Treatment receiving B @ 2.25 kg ha-1 produced the highest grain yield (4.22 t ha-1) which was statistically identical with that obtained with 1.75 kg B ha-1. However, the crop response curve showed 1.90 kg ha-1 to be the optimum boron rate for the maximization of wheat yield. The lowest grain yield (2.84 t/ha) was recorded with control treatment. There was a positive relationship between grain yield and number of grains spike-1. Boron had significant influence on N, P, K, S and B uptake by the crop which, in deed, was more influenced by crop yield and less by nutrient concentration, except N and B uptake where concentration had more influence than yield. DOI: http://dx.doi.org/10.3329/jbau.v9i2.10987 J. Bangladesh Agril. Univ. 9(2): 205210, 2011